An Octahedral Cobalt(III) Complex with Axial NH3 Ligands that Templates and Selectively Stabilises G‐quadruplex DNA. Issue 41 (3rd July 2019) - Ruehl, Carmen L.; Lim, Aaron H. M.; Kench, Timothy; Mann, David J.; Vilar, Ramon
Abstract: Guanine‐rich sequences of DNA are known to readily fold into tetra‐stranded helical structures known as G‐quadruplexes (G4). Due to their biological relevance, G4s are potential anticancer drug targets and therefore there is significant interest in molecules with high affinity for these structures. Most G4 binders are polyaromatic planar compounds which π–π stack on the G4′s guanine tetrad. However, many of these compounds are not very selective since they can also intercalate into duplex DNA. Herein we report a new class of binder based on an octahedral cobalt(III) complex that binds to G4 via a different mode involving hydrogen bonding, electrostatic interactions and π–π stacking. We show that this new compound binds selectivity to G4 over duplex DNA (particularly to the G‐rich sequence of the c‐myc promoter). This new octahedral complex also has the ability to template the formation of G4 DNA from the unfolded sequence. Finally, we show that upon binding to G4, the complex prevents helicase Pif1‐p from unfolding the c‐myc G4 structure. Abstract : G‐quadruplex DNA structures have been identified as potential anticancer drug targets and therefore there is significant interest in molecules with high affinity for these structures. Most G‐quadruplex binders are polyaromatic planar compounds which π–π stack on the G4′s guanine tetrad. Herein we report a new class of binder based on an octahedral cobalt(III) complex that interacts with G‐quadruplexes via a different mode involving hydrogen‐bonding, electrostatic interactions and π–π stacking. We show that this new compound binds selectivity to G4 over duplex DNA and has the ability to template the formation of G4 DNA from the unfolded sequence.